2004
DOI: 10.1111/j.1600-0897.2004.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Expression of Intercellular Adhesion Molecule‐1 (ICAM‐1) and Regulation by Interferon‐Gamma during the Pathogenesis of Endometriosis

Abstract: The ICAM-1 expression in visually normal peritoneal cells from women with endometriosis may play a role in the early implantation of peritoneal endometriosis. Peritoneal INF-gamma stimulation is significantly associated with ICAM-1 expression in endometriosis. Therefore, the differential expression and changes of ICAM-1 may be involved in the mechanism that can escape immunosurveillance and allow refluxed endometrial cells to spread and invade other location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 25 publications
5
25
0
4
Order By: Relevance
“…The fact that TNF produced a strong augmentation of ICAM1 protein in both endometrial cell homogenates is in accord with other studies (Rothlein et al 1988, Vigano et al 1994, Thomson et al 1999, Wu et al 2004) that demonstrate the strong ICAM1 induction mediated by proinflammatory cytokines in endometrial cultures, stimulation not observed on its mRNA suggesting posttranscriptional regulation of ICAM1 in long period of cell culture. Among the possible pathways by which TNF could mediate this increase is through the NFKB1 pathway, as it has been described in ectopic endometrial lesions in patients with endometriosis (Gonzalez-Ramos et al 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The fact that TNF produced a strong augmentation of ICAM1 protein in both endometrial cell homogenates is in accord with other studies (Rothlein et al 1988, Vigano et al 1994, Thomson et al 1999, Wu et al 2004) that demonstrate the strong ICAM1 induction mediated by proinflammatory cytokines in endometrial cultures, stimulation not observed on its mRNA suggesting posttranscriptional regulation of ICAM1 in long period of cell culture. Among the possible pathways by which TNF could mediate this increase is through the NFKB1 pathway, as it has been described in ectopic endometrial lesions in patients with endometriosis (Gonzalez-Ramos et al 2007).…”
Section: Discussionsupporting
confidence: 90%
“…These results coincide with previous studies using cytokines such as IL1B and IFNG, which augmented the normal release of sICAM1 in endometrial stromal cells, with the concentration also significantly greater in cell cultures from ectopic and eutopic endometria of patients with endometriosis than in controls (Somigliana et al 1996, Wu et al 2004, Mangioni et al 2005. It is possible that the increased cleavage of ICAM1 could be mediated by activation of proteases such as MMPs, which are strongly activated by various cytokines, including TNF (Curry & Osteen 2003).…”
Section: Discussionsupporting
confidence: 90%
“…The participation of this cytokine in the pathogenesis of endometriosis has already been described, specifically its ability to enhance resistance of endometrial cells to apoptosis, which would increase the chance of these cells to survive and be implanted outside the uterus (Nishida et al, 2005) and to stimulate the expression of cell adhesion molecules (e.g. ICAM-1), which would allow cells from retrograde menstruation to spread and invade other sites (Wu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional expression of intercellular adhesion molecule 1 (ICAM-1) is up-regulated in endometriosis lesions, a fact that might contribute to early implantation of peritoneal endometriosis (Wu et al, 2004). The inflammatory cytokines interferon γ (IFNγ) and IL-1β induce ICAM-1 protein expression and the secretion of the soluble form of ICAM-1, which competitively inhibits ICAM-mediated cytotoxicity thus increasing survival.…”
Section: Viable Endometrial Cells In the Peritoneal Cavitymentioning
confidence: 99%